Anti-corrosion engine coolant and preparation method thereof
The preparation of stabilizers and dispersants through hydrothermal reaction and coating technology has solved the toxicity, scope of application and stability of existing engine coolant corrosion inhibitors, and achieved efficient anti-corrosion, defoaming and stability effects.
Patent Information
- Application Number
- CN202510138188.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-08
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-02-08
AI Technical Summary
The corrosion inhibitors of existing engine coolant are toxic, have limited scope of application, have high environmental impact, poor stability, high pollution and high usage, and the composite corrosion inhibitors have shortcomings in hard water stability and high temperature stability.
The stabilizer and dispersant are prepared by hydrothermal reaction and coating technology. The thermal conductivity of the coolant and the density of the passivation film are improved by the composite of graphene oxide, alumina and sodium polyacrylate. Polyaspartic acid is used as a linking agent to improve the water solubility and dispersion of the stabilizer, and polyethylene glycol 400 is used as a dispersant to improve the defoaming effect.
It achieves good corrosion resistance, hard water stability, defoaming effect and high temperature stability of anti-corrosion engine coolant, avoiding cavernous and foam tendency problems.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of engine coolant, and in particular to an anti-corrosion engine coolant and a preparation method thereof. Background Art
[0002] Engine coolant, also known as engine antifreeze, is mainly used to protect the normal operation of the engine. Engine coolant can circulate in the engine water tank to play the role of cooling, antifreeze, anti-boiling, anti-scaling, anti-corrosion, etc. It is an indispensable heat dissipation medium for the normal operation of the engine. Most engine antifreeze is red or green in color to facilitate the observation of whether there is leakage of engine antifreeze.
[0003] Engine coolant includes antifreeze, additives, and deionized water. Antifreeze is mainly ethylene glycol or propylene glycol. Additives mainly include corrosion inhibitors, scale inhibitors, defoamers, pigments, etc. Among them, corrosion inhibitors are the most important additives. Existing corrosion inhibitors are divided into inorganic corrosion inhibitors and organic corrosion inhibitors. Inorganic corrosion inhibitors mainly include nitrites, nitrates, silicates, phosphates, molybdates, borax, etc. Organic corrosion inhibitors mainly include benzotriazole, organic carboxylic acids, sodium benzoate, etc.
[0004] Among inorganic corrosion inhibitors, nitrite can form a passivation film on the surface of steel and iron, but nitrite is toxic; nitrate can also form a passivation film on the surface of steel and iron, but nitrate has a strong oxidizing effect only under high temperature conditions or in an acidic environment; silicate can form a passivation film on the surface of aluminum and aluminum alloys, but silicate is easy to precipitate; phosphate can form a dense phosphate film on the surface of steel, iron and aluminum, but phosphate will increase the biochemical oxygen demand and chemical oxygen demand in the water, causing water pollution, and phosphate is also easy to combine with calcium ions and magnesium ions to form precipitation, affecting the anti-scaling effect of the coolant; molybdate can be adsorbed on the defects of the passivation film on the metal surface or enter the interior of the passivation film and work together with it to improve the density of the passivation film; borax can form a passivation film on the metal surface, but borax is toxic. In organic corrosion inhibitors, the hydrogen in benzotriazole can be replaced with the copper ions on the copper surface, and then combined with other benzotriazoles through coordination bonds to form a protective film on the copper surface; organic carboxylic acids can be adsorbed on the metal surface through polar groups to form a protective film; the benzoate in sodium benzoate can be combined with the metal ions on the metal surface through coordination bonds to form a protective film on the metal surface. At the same time, sodium benzoate also has reducing properties, which can reduce the oxidized part of the metal surface and prevent the metal surface from continuing to corrode.
[0005] It can be seen from the corrosion inhibition mechanism and existing problems of the above-mentioned inorganic corrosion inhibitors and organic corrosion inhibitors that the existing inorganic corrosion inhibitors have the disadvantages of being toxic, having a limited scope of application, being greatly affected by the environment in terms of corrosion inhibition, having poor stability, being highly polluting, and having a large dosage. In addition, inorganic corrosion inhibitors need to form a passivation film, i.e., a metal oxide film, on the metal surface. The formation time of the passivation film is long, and it is difficult to achieve short-term protection. Organic corrosion inhibitors mainly quickly bind to the metal surface through coordination or adsorption to form a precipitation film or an adsorption film, which can achieve short-term protection and has a small dosage. However, the density of the protective film formed through coordination or adsorption is poor, resulting in that the organic corrosion inhibitors are inferior to the inorganic corrosion inhibitors in terms of corrosion protection effect. Organic corrosion inhibitors are also prone to generate bubbles, which leads to easy cavitation during use. In addition, the organic carboxylic acids in the organic corrosion inhibitors are easily combined with the calcium ions and magnesium ions in the hard water to form a precipitate, resulting in the poor hard water stability of the organic corrosion inhibitors.
[0006] Based on the above problems, the most commonly used method at present is to compound inorganic corrosion inhibitors and organic corrosion inhibitors to obtain compound corrosion inhibitors, and use the inorganic corrosion inhibitors in the compound corrosion inhibitors to form a dense passivation film on the metal surface to reduce the influence of ambient temperature on the anti-corrosion effect, use the organic corrosion inhibitors in the compound corrosion inhibitors to achieve short-term protection, and increase the amount of defoaming agent in the compound corrosion inhibitor to avoid the generation of bubbles as much as possible. However, it was found in the compounding that there are the following problems: First, after the inorganic corrosion inhibitors and organic corrosion inhibitors are mixed, the synergistic effect is poor. Specifically, since the role of organic corrosion inhibitors in the formation of the passivation film is small, the effect of reducing the amount of inorganic corrosion inhibitors is not obvious. In order to improve the anti-corrosion effect, it is necessary to ensure the amount of inorganic corrosion inhibitors and organic corrosion inhibitors at the same time, but it will lead to a large amount of additives, affecting the cooling effect of the engine coolant; second, excessive use of defoaming agent will affect the cooling effect of the engine coolant; third, because the organic carboxylic acid in the organic corrosion inhibitor is still easy to react with calcium ions and magnesium in hard water Ions combine to form precipitation, resulting in poor hard water stability of the compound corrosion inhibitor; Fourth, there is a mutual influence between inorganic corrosion inhibitors and organic corrosion inhibitors. For example, after mixing silicates with organic carboxylic acids, the organic carboxylic acids will promote the conversion of silicate ions in the silicates into silicic acid, and the silicic acid will aggregate to form silicic acid gel, resulting in poor stability of the compound corrosion inhibitor. Although siloxane compounds can be added as silicate stabilizers and silicane compounds can interact with silicic acid to avoid aggregation of silicic acid, the effect of the silicate stabilizer is greatly affected by temperature, affecting the high-temperature stability of the compound corrosion inhibitor. Summary of the invention
[0007] In view of the deficiencies in the prior art, the present invention provides an anti-corrosion engine coolant and a preparation method thereof. The prepared engine coolant has good anti-corrosion effect, good hard water stability, is not prone to cavitation during use, has good defoaming effect, good cooling effect, and good high-temperature stability.
[0008] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows:
[0009] A method for preparing an anti-corrosion engine coolant comprises: preparing a stabilizer, preparing a dispersant, and mixing materials;
[0010] The method for preparing the stabilizer comprises: hydrothermal reaction and coating;
[0011] The hydrothermal reaction comprises mixing ethylene glycol and deionized water, stirring at room temperature at a stirring speed of 50-100 rpm for 30-40 min, adding graphene oxide, and stirring for 1-1.5 h to obtain a graphene oxide dispersion; mixing aluminum chloride and deionized water, stirring at room temperature at a stirring speed of 50-100 rpm for 15-20 min, dropping sodium hydroxide solution until the pH value is 7-8, and continuing to stir for 5-10 min after the dropping is completed to obtain an aluminum source; mixing sodium polyacrylate and deionized water, stirring at room temperature at a stirring speed of 50-100 rpm for 30-40 min to obtain a sodium polyacrylate solution; mixing the graphene oxide dispersion and the aluminum source, stirring at room temperature at a stirring speed of 50-100 rpm for 30-40 min, dropping the sodium polyacrylate solution, and continuing to stir for 5-10 min after the dropping is completed, and then performing a hydrothermal reaction, centrifuging at a centrifugal speed of 5000-6000 rpm for 5-6 min, taking a precipitate, washing it with deionized water, and drying it to obtain a composite powder;
[0012] In the hydrothermal reaction, the amount ratio of ethylene glycol, deionized water and graphene oxide in the graphene oxide dispersion is 20-25 g: 140-150 mL: 30 g;
[0013] The dosage ratio of aluminum chloride and deionized water in the aluminum source is 400-410 g: 2300-2400 mL;
[0014] The sodium polyacrylate aqueous solution has a dosage ratio of 30-32 g to deionized water: 500-600 mL;
[0015] The mass ratio of graphene oxide in the graphene oxide dispersion, aluminum chloride in the aluminum source, and sodium polyacrylate in the sodium polyacrylate aqueous solution is 30:400-410:30-32;
[0016] The particle size of the graphene oxide is 500 nm;
[0017] The mass concentration of the sodium hydroxide solution is 10%;
[0018] The number average molecular weight of the sodium polyacrylate is 5000;
[0019] The dropping speed of the sodium hydroxide solution is 4-5 mL / min;
[0020] The dropping speed of the sodium polyacrylate solution is 20-30 mL / min;
[0021] The temperature of the hydrothermal reaction is 140-150°C and the time is 5-6h;
[0022] The coating comprises mixing the composite powder and deionized water, stirring the mixture at a stirring speed of 50-100 rpm for 30-40 minutes at room temperature to obtain a composite powder dispersion; mixing polyaspartic acid and deionized water, stirring the mixture at a stirring speed of 50-100 rpm for 10-15 minutes at room temperature to obtain a polyaspartic acid solution; stirring the composite powder dispersion at a stirring speed of 100-150 rpm at room temperature, then dropping the polyaspartic acid solution, continuing to stir for 1.5-2 hours after the dropping is completed, centrifuging at a centrifugal speed of 5000-6000 rpm for 5-6 minutes, taking a precipitate, washing it with deionized water and drying it to obtain a stabilizer;
[0023] In the coating, the ratio of the composite powder to deionized water in the composite powder dispersion is 140-150 g: 1300-1500 mL;
[0024] The dosage ratio of polyaspartic acid to deionized water in the polyaspartic acid solution is 13-15 g: 290-300 mL;
[0025] The mass ratio of the composite powder in the composite powder dispersion to the polyaspartic acid in the polyaspartic acid solution is 140-150:13-15;
[0026] The dropping speed of the polyaspartic acid solution is 20-30 mL / min;
[0027] The dispersant is prepared by mixing the composite powder and deionized water, stirring at a stirring speed of 50-100 rpm for 30-40 min at room temperature, dropping polyethylene glycol 400, continuing to stir for 2-2.5 h after the dropping is completed, centrifuging at a centrifugal speed of 5000-6000 rpm for 5-6 min, taking the precipitate, washing it with deionized water and drying it to obtain the dispersant;
[0028] In the preparation of the dispersant, the usage ratio of the composite powder, deionized water, and polyethylene glycol 400 is 100-110 g: 1500-1700 mL: 30-32 mL;
[0029] The composite powder is the composite powder obtained in the hydrothermal reaction step in the step of preparing the stabilizer;
[0030] The dropping speed of the polyethylene glycol 400 is 3-4 mL / min;
[0031] The mixing material comprises mixing ethylene glycol and deionized water, stirring at room temperature at a stirring speed of 200-300 rpm for 10-15 minutes, adding isooctanoic acid, undecanoic acid, suberic acid, sodium gluconate, sodium benzoate, methylbenzotriazole, sodium hydroxide, a stabilizer, and a dispersant, and continuing to stir for 20-30 minutes, adding sodium metasilicate nonahydrate, 3-(trihydroxymethylsiloxane)-propane-monophosphate phosphate, sodium nitrate, and sodium molybdate, and continuing to stir for 20-30 minutes, adding an organosilicon defoamer and rhodamine B, and continuing to stir for 100-120 minutes to obtain an anti-corrosion engine coolant;
[0032] In the mixture, the mass ratio of ethylene glycol, deionized water, isooctanoic acid, undecanoic acid, suberic acid, sodium gluconate, sodium benzoate, methylbenzotriazole, sodium hydroxide, stabilizer, dispersant, sodium metasilicate nonahydrate, 3-(trihydroxymethylsiloxane)-propane-monophosphate phosphate, sodium nitrate, sodium molybdate, silicone defoamer, and rhodamine B is 950-1000:630-670:4-4.5:4-4.2:3.6-4:3.8-4:2.7-3:0.5-0.6:3.8-4:1.4-1.5:0.9-1:3.4-3.6:1-1.2:2.4-2.5:2-2.1:0.15-0.16:0.1-0.11.
[0033] An anti-corrosion engine coolant prepared by the above-mentioned preparation method.
[0034] Compared with the prior art, the present invention has the following beneficial effects:
[0035] (1) The method for preparing the anti-corrosion engine coolant of the present invention comprises preparing a stabilizer, preparing a dispersant, and mixing. The preparation of the stabilizer comprises a hydrothermal reaction and a coating. The hydrothermal reaction comprises treating graphene oxide with ethylene glycol to promote the dispersion of graphene oxide to obtain a graphene oxide dispersion liquid. Then, aluminum chloride is dissolved in deionized water, and a precipitant sodium hydroxide is added to obtain an aluminum source. Then, sodium polyacrylate is dissolved in deionized water to obtain a sodium polyacrylate solution. Finally, the graphene oxide dispersion liquid, the aluminum source, and the sodium polyacrylate solution are mixed and subjected to a hydrothermal reaction to obtain a composite of graphene oxide, aluminum oxide, and sodium polyacrylate, i.e., a composite powder. The coating comprises dispersing the composite powder in deionized water to obtain a composite powder dispersion liquid. Then, polyaspartic acid is dissolved in deionized water to obtain a polyaspartic acid solution. , and then mixing the composite powder dispersion with the polyaspartic acid solution, and the polyaspartic acid is adsorbed on the surface of the composite powder to obtain a stabilizer; the graphene oxide in the stabilizer can improve the thermal conductivity of the coolant, the aluminum oxide can be adsorbed on the metal surface, and the density of the passivation film can be improved, the sodium polyacrylate can chelate calcium ions and magnesium ions, and improve the hard water resistance stability of the coolant, and the polyaspartic acid can improve the water solubility and dispersibility of the stabilizer, and can also be used as a linker to fix the stabilizer on the metal surface; the preparation of the dispersant is to mix the composite powder obtained in the preparation of the stabilizer with polyethylene glycol 400, and the polyethylene glycol 400 is adsorbed on the surface of the composite powder to obtain the dispersant, and the polyethylene glycol 400 on the surface of the dispersant can improve the water solubility and dispersibility of the dispersant, and can also be adsorbed on the surface of the formed foam, so as to improve the defoaming effect of the coolant;
[0036] (2) The method for preparing an anti-corrosion engine coolant of the present invention has good anti-corrosion effect. The anti-corrosion effect is tested by a method of simulating corrosion (88°C, 1064h). The mass change of the copper test piece is from +1.1mg to +2.3mg, the mass change of the brass test piece is from +2.1mg to +2.9mg, the mass change of the steel test piece is from +1.4mg to +2.0mg, the mass change of the cast iron test piece is from +1.9mg to +2.4mg, the mass change of the solder test piece is from +1.6mg to +2.5mg, and the mass change of the cast aluminum test piece is from +0.7mg to +1.0mg.
[0037] (3) The method for preparing the anti-corrosion engine coolant of the present invention has good hard water stability, and the hard water resistance stability (90°C, 336h) precipitate volume is 0mL;
[0038] (4) The method for preparing the anti-corrosion engine coolant of the present invention, wherein the prepared engine coolant is not prone to cavitation during use, and the cavitation corrosion of the aluminum pump (113°C, 103 kPa, 100h) is level 9;
[0039] (5) The method for preparing the anti-corrosion engine coolant of the present invention has good defoaming effect, the foam volume in the foam tendency (88°C) is 38-42mL, and the foam disappearance time is 0.8-0.9s;
[0040] (6) The method for preparing the anti-corrosion engine coolant of the present invention has good cooling effect and a thermal conductivity of 0.535-0.558 W / (m•K) at 25°C;
[0041] (7) The method for preparing the anti-corrosion engine coolant of the present invention has good high temperature stability, and the mass change in the heat transfer corrosion of cast aluminum alloy (135°C, 168h) is -0.3mg / cm 2 To -0.2mg / cm 2 , the amount of solution precipitation after the test is 0-0.01mL. DETAILED DESCRIPTION
[0042] In order to have a clearer understanding of the technical features, purposes and effects of the present invention, the specific implementation methods of the present invention are now described.
[0043] Example 1
[0044] A method for preparing an anti-corrosion engine coolant, specifically comprising:
[0045] 1. Preparation of stabilizer:
[0046] (1) Hydrothermal reaction: 20 g of ethylene glycol and 140 mL of deionized water were mixed, and the mixture was stirred at 50 rpm for 30 min at room temperature. 30 g of graphene oxide was added, and the mixture was stirred for 1 h to obtain a graphene oxide dispersion. 400 g of aluminum chloride and 2300 mL of deionized water were mixed, and the mixture was stirred at 50 rpm for 15 min at room temperature. Sodium hydroxide solution was added dropwise until the pH value was 7, and the dropping speed was controlled to 4 mL / min. After the addition was completed, the mixture was stirred for 5 min to obtain an aluminum source. 30 g of sodium polyacrylate and 500 mL of deionized water were added. After mixing with water, stirring at a stirring speed of 50 rpm for 30 minutes at room temperature to obtain a sodium polyacrylate solution; after mixing the above-mentioned graphene oxide dispersion with the above-mentioned aluminum source, stirring at a stirring speed of 50 rpm for 30 minutes at room temperature, adding the above-mentioned sodium polyacrylate solution dropwise, controlling the dropping speed to 20 mL / min, and continuing to stir for 5 minutes after the addition is completed to obtain a mixed solution; hydrothermally reacting the above-mentioned mixed solution at 140° C. for 5 hours, centrifuging at a centrifugal speed of 5000 rpm for 5 minutes, taking the precipitate, washing it with deionized water and drying it to obtain a composite powder;
[0047] The particle size of the graphene oxide is 500 nm;
[0048] The mass concentration of the sodium hydroxide solution is 10%;
[0049] The number average molecular weight of the sodium polyacrylate is 5000;
[0050] (2) Coating: 140 g of composite powder and 1300 mL of deionized water were mixed, and the mixture was stirred at a stirring speed of 50 rpm for 30 min at room temperature to obtain a composite powder dispersion; 13 g of polyaspartic acid and 290 mL of deionized water were mixed, and the mixture was stirred at a stirring speed of 50 rpm for 10 min at room temperature to obtain a polyaspartic acid solution; the composite powder dispersion was stirred at a stirring speed of 100 rpm at room temperature, and then the polyaspartic acid solution was added dropwise at a dropping speed of 20 mL / min. After the addition was completed, the mixture was stirred for 1.5 h, and the mixture was centrifuged at a centrifugal speed of 5000 rpm for 5 min. The precipitate was taken, washed with deionized water, and then dried to obtain a stabilizer;
[0051] 2. Prepare a dispersant: Mix 100 g of the composite powder obtained in the hydrothermal reaction of step (1) in the preparation of the stabilizer in step 1 and 1500 mL of deionized water, stir at room temperature at a stirring speed of 50 rpm for 30 min, add 30 mL of polyethylene glycol 400 dropwise, control the dropping speed to 3 mL / min, continue stirring for 2 h after the addition is completed, centrifuge at a centrifugal speed of 5000 rpm for 5 min, take the precipitate, wash it with deionized water and dry it to obtain a dispersant;
[0052] 3. Mixing: After mixing 950g of ethylene glycol and 630g of deionized water, stir at room temperature at a stirring speed of 200rpm for 10min, add 4g of isooctanoic acid, 4g of undecanoic acid, 3.6g of suberic acid, 3.8g of sodium gluconate, 2.7g of sodium benzoate, 0.5g of methylbenzotriazole, 3.8g of sodium hydroxide, 1.4g of stabilizer, 0.9g of dispersant, continue stirring for 20min, add 3.4g of sodium metasilicate nonahydrate, 1g of 3-(trihydroxymethylsiloxane)-propane-monophosphate·phosphate, 2.4g of sodium nitrate, 2g of sodium molybdate, continue stirring for 20min, add 0.15g of organosilicon defoamer and 0.1g of rhodamine B, continue stirring for 100min, and obtain an anti-corrosion engine coolant.
[0053] This embodiment also provides an anti-corrosion engine coolant prepared by the aforementioned preparation method.
[0054] Example 2
[0055] A method for preparing an anti-corrosion engine coolant, specifically comprising:
[0056] 1. Preparation of stabilizer:
[0057] (1) Hydrothermal reaction: 22 g of ethylene glycol and 145 mL of deionized water were mixed, and the mixture was stirred at 80 rpm for 35 min at room temperature. 30 g of graphene oxide was added, and the mixture was stirred for 1 h to obtain a graphene oxide dispersion. 405 g of aluminum chloride and 2350 mL of deionized water were mixed, and the mixture was stirred at 80 rpm for 18 min at room temperature. Sodium hydroxide solution was added dropwise until the pH value was 7.5, and the dropping speed was controlled to 5 mL / min. After the addition was completed, the stirring was continued for 8 min to obtain an aluminum source. 31 g of sodium polyacrylate and 550 mL of deionized water were added. After mixing with water, stirring at a stirring speed of 80 rpm for 35 minutes at room temperature to obtain a sodium polyacrylate solution; after mixing the above-mentioned graphene oxide dispersion with the above-mentioned aluminum source, stirring at a stirring speed of 80 rpm for 35 minutes at room temperature, adding the above-mentioned sodium polyacrylate solution dropwise, controlling the dropping speed to 25 mL / min, and continuing to stir for 8 minutes after the addition is completed to obtain a mixed solution; hydrothermally reacting the above-mentioned mixed solution at 145° C. for 5.5 hours, centrifuging at a centrifugal speed of 5500 rpm for 5 minutes, taking the precipitate, washing it with deionized water and drying it to obtain a composite powder;
[0058] The particle size of the graphene oxide is 500 nm;
[0059] The mass concentration of the sodium hydroxide solution is 10%;
[0060] The number average molecular weight of the sodium polyacrylate is 5000;
[0061] (2) Coating: 145 g of composite powder and 1400 mL of deionized water were mixed, and the mixture was stirred at a stirring speed of 80 rpm for 35 min at room temperature to obtain a composite powder dispersion; 14 g of polyaspartic acid and 295 mL of deionized water were mixed, and the mixture was stirred at a stirring speed of 80 rpm for 12 min at room temperature to obtain a polyaspartic acid solution; the composite powder dispersion was stirred at a stirring speed of 100 rpm at room temperature, and then the polyaspartic acid solution was added dropwise at a dropping speed of 25 mL / min. After the addition was completed, the mixture was stirred for 1.5 h, and the mixture was centrifuged at a centrifugal speed of 5500 rpm for 5 min. The precipitate was taken, washed with deionized water, and then dried to obtain a stabilizer;
[0062] 2. Prepare a dispersant: Mix 105 g of the composite powder obtained in the hydrothermal reaction of step (1) in the preparation of the stabilizer in step 1 and 1600 mL of deionized water, stir at room temperature at a stirring speed of 80 rpm for 35 min, add 31 mL of polyethylene glycol 400 dropwise, control the dropping speed to 4 mL / min, continue stirring for 2 h after the addition is completed, centrifuge at a centrifugal speed of 5500 rpm for 5 min, take the precipitate, wash it with deionized water and dry it to obtain a dispersant;
[0063] 3. Mixing: After mixing 980g of ethylene glycol and 650g of deionized water, stir at room temperature at a stirring speed of 250rpm for 12min, add 4.2g of isooctanoic acid, 4g of undecanoic acid, 3.8g of suberic acid, 3.9g of sodium gluconate, 2.8g of sodium benzoate, 0.5g of methylbenzotriazole, 3.9g of sodium hydroxide, 1.4g of stabilizer, 1g of dispersant, continue stirring for 25min, add 3.5g of sodium metasilicate nonahydrate, 1.1g of 3-(trihydroxymethylsiloxane)-propane-monophosphate·phosphate, 2.5g of sodium nitrate, 2g of sodium molybdate, continue stirring for 25min, add 0.15g of organosilicon defoamer and 0.1g of rhodamine B, continue stirring for 110min, and obtain an anti-corrosion engine coolant.
[0064] This embodiment also provides an anti-corrosion engine coolant prepared by the aforementioned preparation method.
[0065] Example 3
[0066] A method for preparing an anti-corrosion engine coolant, specifically comprising:
[0067] 1. Preparation of stabilizer:
[0068] (1) Hydrothermal reaction: 25 g of ethylene glycol and 150 mL of deionized water were mixed, and the mixture was stirred at 100 rpm for 40 min at room temperature. 30 g of graphene oxide was added, and the mixture was stirred for 1.5 h to obtain a graphene oxide dispersion. 410 g of aluminum chloride and 2400 mL of deionized water were mixed, and the mixture was stirred at 100 rpm for 20 min at room temperature. Sodium hydroxide solution was added dropwise until the pH value was 8, and the dropping speed was controlled to 5 mL / min. After the addition was completed, the mixture was stirred for 10 min to obtain an aluminum source. 32 g of sodium polyacrylate and 600 mL of deionized water were added. After mixing with water, stirring at a stirring speed of 100 rpm for 40 minutes at room temperature to obtain a sodium polyacrylate solution; after mixing the above-mentioned graphene oxide dispersion with the above-mentioned aluminum source, stirring at a stirring speed of 100 rpm for 40 minutes at room temperature, adding the above-mentioned sodium polyacrylate solution dropwise, controlling the dropping speed to 30 mL / min, and continuing to stir for 10 minutes after the dropping is completed to obtain a mixed solution; hydrothermally reacting the above-mentioned mixed solution at 150° C. for 6 hours, centrifuging at a centrifugal speed of 6000 rpm for 6 minutes, taking the precipitate, washing it with deionized water and drying it to obtain a composite powder;
[0069] The particle size of the graphene oxide is 500 nm;
[0070] The mass concentration of the sodium hydroxide solution is 10%;
[0071] The number average molecular weight of the sodium polyacrylate is 5000;
[0072] (2) Coating: 150 g of composite powder and 1500 mL of deionized water were mixed, and the mixture was stirred at a stirring speed of 100 rpm for 40 min at room temperature to obtain a composite powder dispersion; 15 g of polyaspartic acid and 300 mL of deionized water were mixed, and the mixture was stirred at a stirring speed of 100 rpm for 15 min at room temperature to obtain a polyaspartic acid solution; the composite powder dispersion was stirred at a stirring speed of 150 rpm at room temperature, and then the polyaspartic acid solution was added dropwise at a dropping speed of 30 mL / min. After the addition was completed, the mixture was stirred for 2 h, and the mixture was centrifuged at a centrifugal speed of 6000 rpm for 6 min. The precipitate was taken, washed with deionized water, and then dried to obtain a stabilizer;
[0073] 2. Prepare a dispersant: Mix 110 g of the composite powder obtained in the hydrothermal reaction of step (1) in the preparation of the stabilizer in step 1 and 1700 mL of deionized water, stir at room temperature at a stirring speed of 100 rpm for 40 min, add 32 mL of polyethylene glycol 400 dropwise, control the dropping speed to 4 mL / min, continue stirring for 2.5 h after the addition is completed, centrifuge at a centrifugal speed of 6000 rpm for 6 min, take the precipitate, wash it with deionized water and dry it to obtain a dispersant;
[0074] 3. Mixing: After mixing 1000g of ethylene glycol and 670g of deionized water, stir at room temperature at a stirring speed of 300rpm for 15min, add 4.5g of isooctanoic acid, 4.2g of undecanoic acid, 4g of suberic acid, 4g of sodium gluconate, 3g of sodium benzoate, 0.6g of methylbenzotriazole, 4g of sodium hydroxide, 1.5g of stabilizer, 1g of dispersant, continue stirring for 30min, add 3.6g of sodium metasilicate nonahydrate, 1.2g of 3-(trihydroxymethylsiloxane)-propane-monophosphate·phosphate, 2.5g of sodium nitrate, 2.1g of sodium molybdate, continue stirring for 30min, add 0.16g of organosilicon defoamer and 0.11g of rhodamine B, continue stirring for 120min, and obtain an anti-corrosion engine coolant.
[0075] This embodiment also provides an anti-corrosion engine coolant prepared by the aforementioned preparation method.
[0076] Comparative Example 1
[0077] Based on the method for preparing the anti-corrosion engine coolant of Example 2, the first step of preparing the stabilizer is omitted, and the use of the stabilizer is omitted in the third step of mixing;
[0078] The rest of the technical solutions are the same as those in Example 2.
[0079] This comparative example also provides an anti-corrosion engine coolant prepared by the aforementioned preparation method.
[0080] Comparative Example 2
[0081] Based on the preparation method of the anti-corrosion engine coolant of Example 2, the second step of preparing the dispersant is omitted, and the use of the dispersant is omitted in the third step of mixing;
[0082] The rest of the technical solutions are the same as those in Example 2.
[0083] This comparative example also provides an anti-corrosion engine coolant prepared by the aforementioned preparation method.
[0084] Comparative Example 3
[0085] On the basis of the preparation method of the anti-corrosion engine coolant of Comparative Example 1, the amount of other raw materials except ethylene glycol and deionized water in the mixing step of step 3 is increased by 20%, and the mixing step of step 3 is specifically changed to:
[0086] 3. Mixing: After mixing 980g of ethylene glycol and 650g of deionized water, stir at room temperature at a stirring speed of 200rpm for 12min, add 5.04g of isooctanoic acid, 4.8g of undecanoic acid, 4.56g of suberic acid, 4.68g of sodium gluconate, 3.36g of sodium benzoate, 0.6g of methylbenzotriazole, 4.68g of sodium hydroxide, and 1.2g of dispersant, and continue stirring for 25min, add 4.2g of sodium metasilicate nonahydrate, 1.32g of 3-(trihydroxymethylsiloxane)-propane-monophosphate·phosphate, 3g of sodium nitrate, and 2.4g of sodium molybdate, and continue stirring for 25min, add 0.18g of organosilicon defoamer and 0.12g of rhodamine B, and continue stirring for 110min to obtain an anti-corrosion engine coolant.
[0087] This comparative example also provides an anti-corrosion engine coolant prepared by the aforementioned preparation method.
[0088] Test Example 1
[0089] The anti-corrosion effects of the anti-corrosion engine coolants prepared in Examples 1-3 and Comparative Examples 1-3 were tested according to the method of simulating corrosion (88°C, 1064h) in GB 29743.1-2022 standard. The test results are as follows:
[0090]
[0091] It can be seen from the above results that the anti-corrosion effect of the anti-corrosion engine coolant prepared in Comparative Examples 1-3 is worse than that of the anti-corrosion engine coolant prepared in Example 2.
[0092] Test Example 2
[0093] The hard water resistance stability of the anti-corrosion engine coolants prepared in Examples 1-3 and Comparative Examples 1-3 was tested according to GB 29743.1-2022 standard, and the test results are as follows:
[0094]
[0095] It can be seen from the above results that the anti-corrosion engine coolant prepared in Comparative Examples 1-3 has a lower hard water resistance stability than the anti-corrosion engine coolant prepared in Example 2.
[0096] Test Example 3
[0097] The cavitation corrosion results of the aluminum pump of the anti-corrosion engine coolant prepared in Examples 1-3 and Comparative Examples 1-3 were tested according to GB 29743.1-2022 standard, and the test results are as follows:
[0098]
[0099] It can be seen from the above results that the aluminum pump cavitation corrosion results of the anti-corrosion engine coolants prepared in Comparative Examples 1-3 are worse than those of the anti-corrosion engine coolant prepared in Example 2.
[0100] Test Example 4
[0101] The defoaming effect of the anti-corrosion engine coolant prepared in Examples 1-3 and Comparative Examples 1-3 was tested according to GB 29743.1-2022 standard, and the test results are as follows:
[0102]
[0103] It can be seen from the above results that the defoaming effect of the anti-corrosion engine coolant prepared in Comparative Example 2 is worse than that of the anti-corrosion engine coolant prepared in Example 2.
[0104] Test Example 5
[0105] The thermal conductivity of the anti-corrosion engine coolants prepared in Examples 1-3 and Comparative Examples 1-3 at 25° C. was tested, and the test results are as follows:
[0106]
[0107] It can be seen from the above results that the thermal conductivity of the anti-corrosion engine coolant prepared in Comparative Examples 1-3 is lower than that of the anti-corrosion engine coolant prepared in Example 2.
[0108] Test Example 6
[0109] The high temperature stability of the anti-corrosion engine coolants prepared in Examples 1-3 and Comparative Examples 1-3 was tested according to GB 29743.1-2022 standard, and the test results are as follows:
[0110]
[0111] It can be seen from the above results that the high temperature stability of the anti-corrosion engine coolant prepared in Comparative Examples 1-3 is worse than that of the anti-corrosion engine coolant prepared in Example 2.
[0112] Unless otherwise specified, all percentages used in the present invention are by mass.
[0113] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing an anti-corrosion engine coolant, characterized in that: include: Preparation of stabilizers, preparation of dispersants, and mixing; The method for preparing the stabilizer comprises: hydrothermal reaction and coating; The hydrothermal reaction comprises mixing ethylene glycol and deionized water, stirring at room temperature, adding graphene oxide, stirring to obtain a graphene oxide dispersion; mixing aluminum chloride and deionized water, stirring at room temperature, adjusting the pH to 7-8, and continuing to stir after the dropwise addition to obtain an aluminum source; mixing sodium polyacrylate and deionized water, stirring at room temperature to obtain a sodium polyacrylate solution; mixing the graphene oxide dispersion and the aluminum source, stirring at room temperature, dropping the sodium polyacrylate solution, continuing to stir after the dropwise addition, and then performing a hydrothermal reaction, centrifuging, taking a precipitate, washing, and drying to obtain a composite powder; The coating comprises mixing the composite powder and deionized water, stirring at room temperature to obtain a composite powder dispersion; mixing polyaspartic acid and deionized water, stirring at room temperature to obtain a polyaspartic acid solution; stirring the composite powder dispersion at room temperature, then dripping the polyaspartic acid solution, continuing to stir after the dripping is completed, centrifuging, taking a precipitate, washing it, and drying it to obtain a stabilizer; The dispersant is prepared by mixing the composite powder and deionized water, stirring at room temperature, dropping polyethylene glycol 400, continuing to stir after the dropping, centrifuging, taking the precipitate, washing and drying to obtain the dispersant.
2. The method for preparing the anti-corrosion engine coolant according to claim 1, characterized in that: In the hydrothermal reaction, the amount ratio of ethylene glycol, deionized water and graphene oxide in the graphene oxide dispersion is 20-25 g: 140-150 mL: 30 g; The dosage ratio of aluminum chloride and deionized water in the aluminum source is 400-410 g: 2300-2400 mL; The sodium polyacrylate aqueous solution has a dosage ratio of 30-32 g to deionized water: 500-600 mL; The mass ratio of graphene oxide in the graphene oxide dispersion, aluminum chloride in the aluminum source, and sodium polyacrylate in the sodium polyacrylate aqueous solution is 30:400-410:30-32.
3. The method for preparing the anti-corrosion engine coolant according to claim 1, characterized in that: In the hydrothermal reaction, the particle size of the graphene oxide is 500 nm; The number average molecular weight of the sodium polyacrylate is 5000; The dropping speed of the sodium polyacrylate solution is 20-30 mL / min; The temperature of the hydrothermal reaction is 140-150° C. and the time is 5-6 hours.
4. The method for preparing the anti-corrosion engine coolant according to claim 1, characterized in that: In the coating, the ratio of the composite powder to deionized water in the composite powder dispersion is 140-150 g: 1300-1500 mL; The dosage ratio of polyaspartic acid to deionized water in the polyaspartic acid solution is 13-15 g: 290-300 mL; The mass ratio of the composite powder in the composite powder dispersion to the polyaspartic acid in the polyaspartic acid solution is 140-150:13-15; The dropping speed of the polyaspartic acid solution is 20-30 mL / min.
5. The method for preparing the anti-corrosion engine coolant according to claim 1, characterized in that: In the preparation of the dispersant, the usage ratio of the composite powder, deionized water, and polyethylene glycol 400 is 100-110 g: 1500-1700 mL: 30-32 mL; The composite powder is the composite powder obtained in the hydrothermal reaction step in the step of preparing the stabilizer; The dropping speed of the polyethylene glycol 400 is 3-4 mL / min.
6. The method for preparing the anti-corrosion engine coolant according to claim 1, characterized in that: The mixing material comprises the following steps: mixing ethylene glycol and deionized water, stirring the mixture at a stirring speed of 200-300 rpm for 10-15 minutes at room temperature, adding isooctanoic acid, undecanoic acid, suberic acid, sodium gluconate, sodium benzoate, methylbenzotriazole, sodium hydroxide, a stabilizer and a dispersant, and continuing to stir the mixture for 20-30 minutes; adding sodium metasilicate nonahydrate, 3-(trihydroxymethylsiloxane)-propane-monophosphate phosphate, sodium nitrate and sodium molybdate, and continuing to stir the mixture for 20-30 minutes; adding an organosilicon defoamer and rhodamine B, and continuing to stir the mixture for 100-120 minutes to obtain an anti-corrosion engine coolant.
7. The method for preparing the anti-corrosion engine coolant according to claim 6, characterized in that: In the mixture, the mass ratio of ethylene glycol, deionized water, isooctanoic acid, undecanoic acid, suberic acid, sodium gluconate, sodium benzoate, methylbenzotriazole, sodium hydroxide, stabilizer, dispersant, sodium metasilicate nonahydrate, 3-(trihydroxymethylsiloxane)-propane-monophosphate phosphate, sodium nitrate, sodium molybdate, silicone defoamer, and rhodamine B is 950-1000:630-670:4-4.5:4-4.2:3.6-4:3.8-4:2.7-3:0.5-0.6:3.8-4:1.4-1.5:0.9-1:3.4-3.6:1-1.2:2.4-2.5:2-2.1:0.15-0.16:0.1-0.
11.
8. An anti-corrosion engine coolant prepared by the preparation method according to any one of claims 1 to 7.
Citation Information
Patent Citations
Organic engine cooling liquid containing carboxylated graphene and preparation method thereof
CN106905932A
Method for preparing silicon-based composite material
CN108899529A
Cited By
High-performance automobile anti-freezing fluid containing nano additive and preparation method of high-performance automobile anti-freezing fluid
CN121628582A